2008
DOI: 10.1007/s11064-008-9877-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypoinsulinemia Alleviates the Grf1/Ras/Akt Anti-Apoptotic Pathway and Induces Alterations of Mitochondrial Ras Trafficking in Neuronal Cells

Abstract: Recent observations have established that interruption of insulin production causes deficits in learning and memory formation. We have studied the mechanism of insulin's neuroprotective effect on primary neuronal cells and in streptozotocin (STZ)-induced diabetic rat brain. We have found that in hippocampal neuronal cells insulin increases the content of farnesylated Ras and phosphorylated form of Akt. Besides, the treatment of cells by insulin leads to the activation of mitochondrial cytochrome oxidase, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Moreover, a positive correlation between elevated neuronal apoptosis in type 1 diabetes and reduced expression of insulin and IGF receptors may also exist [272]. Zhuravliova et al [273] reported that hypoinsulinemia causes regulatory proteins to be redistributed between intracellular compartments. For instance, the content of Grf1 bound to membrane and mitochondrial Ras are reduced in response to hypoinsulinemia.…”
Section: Protective Effects Against Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a positive correlation between elevated neuronal apoptosis in type 1 diabetes and reduced expression of insulin and IGF receptors may also exist [272]. Zhuravliova et al [273] reported that hypoinsulinemia causes regulatory proteins to be redistributed between intracellular compartments. For instance, the content of Grf1 bound to membrane and mitochondrial Ras are reduced in response to hypoinsulinemia.…”
Section: Protective Effects Against Apoptosismentioning
confidence: 99%
“…Ras is the mediator of Akt activation by PI3K that eventually induces phosphorylation of various proteins such as mitochondrial antiapoptotic proteins. So, Ras inhibition by insulin deficiencies is thought to promote neuronal apoptosis [273]. Baek et al have also reported that insulin withdrawal from HCN cells derived from adult rat brain induces autophagic cell death [274].…”
Section: Protective Effects Against Apoptosismentioning
confidence: 99%
“…RASGRF1 is induced by cocaine, which promotes Ras-Mapk signaling in the nucleus accumbens [25] and is important for phospho-CREB signaling [26] and ΔFosB accumulation [27], both of which are important for cocaine behavior.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 ] Insulin partially protected against glutamate decreased cell viability in cultured neuronal cells. [ 10 11 ] Fanne et al . found, insulin decreased glutamate levels in the cerebral spinal fluid of rats, decreased infarct size and improved neuro-scoring.…”
Section: E Ffect Of I Nsulin On the mentioning
confidence: 99%